2022
DOI: 10.3390/foods11050746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biological Potential of Himanthalia elongata (L.) S.F.Gray and Eisenia bicyclis (Kjellman) Setchell Subcritical Water Extracts

Abstract: Neuroprotection is a need that remains unmet in treating chronic neurodegenerative disorders, despite decades of extensive research. To find new neuroprotective compounds, extracts of Himanthalia elongata (L.) S.F.Gray and of Eisenia bicyclis (Kjellman) Setchell were obtained through subcritical water extraction applying a four-step temperature gradient. The fractions obtained were screened against brain enzymes involved in neurodegenerative etiology, namely in Alzheimer’s and Parkinson’s diseases, and against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…For the FRAP assay, calibration was performed with AA (linearity range: 10-100 mg/L, R 2 > 0.9989), and the results were expressed in mg of AA equivalents per g of dw (mg AAE/g dw). The ABTS protocol was performed as previously described by Pinto et al [27]. The calibration curve (linearity range: 5-50 mg/L, R 2 > 0.9994) was obtained using AA, and the results were expressed as mg AAE/g dw.…”
Section: Dpph-rsa Frap and Abts Assaysmentioning
confidence: 99%
“…For the FRAP assay, calibration was performed with AA (linearity range: 10-100 mg/L, R 2 > 0.9989), and the results were expressed in mg of AA equivalents per g of dw (mg AAE/g dw). The ABTS protocol was performed as previously described by Pinto et al [27]. The calibration curve (linearity range: 5-50 mg/L, R 2 > 0.9994) was obtained using AA, and the results were expressed as mg AAE/g dw.…”
Section: Dpph-rsa Frap and Abts Assaysmentioning
confidence: 99%
“…A spectrophotometric assay based on the Folin-Ciocalteu reagent [12] was employed to determine the TPC values of each extract, and calibration curves were performed using gallic acid. The formation of the blue complex was monitored at 760 nm in a microplate reader (Synergy HT, Biotek Instruments, Winooski, VT, USA).…”
Section: Determination Of Total Phenolic Compounds (Tpc)mentioning
confidence: 99%
“…The antiradical capacity was assessed against two radicals, namely, DPPH • and ABTS •+ , according to well-established procedures [12]. Absorbances were monitored in a microplate reader (Synergy HT, Biotek Instruments, Winooski, VT, USA) at 517 and 734 nm, respectively.…”
Section: Antiradical Acitvitymentioning
confidence: 99%
“…Concerning step 4 fraction obtained at higher temperatures (190-250 • C), Maillard reaction, caramelization and thermo-oxidation occurred, and products such as melanoidins are responsible for the antioxidant capacity and the neuroprotective effects. The same SWE conditions described previously [34] (four steps, different temperatures) were applied by Gomes et al [75] to H. elongata and E. bicyclis. These authors observed that, although no significant enzyme inhibition was detected, fractions 3 and 4 presented the highest biological activities, namely DPPH • , ABTS •+ , • NO, and O 2…”
Section: Pressurised Liquid Extraction (Ple)mentioning
confidence: 99%